Estudio de la abeja sin aguijón de la tribu (meliponini) de la parte alta (transecto i) de la microcuenca del río Yungañan. - Molina Jácome, Rolando David (2020)
This project was carried out in the parish of La Esperanza, canton Pujili, In the river microbasin Yungañan between 1300 and 1500 m.a.s.l. having as objectives: To establish the presence of stingless bees of the tribe Meliponini in the area; Thus identify the presences of stingless bee species on the top side of the river Yungañan. However to determine the presence of stingless bees, three types of trapping were performed: Malayse, Harris, Plates and the use of entomological network, for identification, dichotonic keys were used at the National Biodiversity Institute INABIO. The results obtained were the following: two types of stingless bees existed that belongs to the species Parapartamona vittigera with 38 individuals and Plebeia sp, with 21 individuals and due to meteorological phenomenon as the high rainfall starting on the month of october with 68,55 mm, november (105,30), december (163,37 mm) and january (420,95 mm), inhibiting the presence of insects in general.